Influence of ultraviolet-C irradiation treatment on quality and shelf life of mung bean sprouts during storage - Tripathi, Abhinav; Meena, Rekha; Sobhanan, Anusree; Koley, Tanmay Kumar; Meghwal, Murlidhar; Maria Giuffrè, Angelo (Italian Journal of Food Science, 2024)
This research analyzed the impact of exposing mung bean sprouts to ultraviolet-C (UV-C) radiation for different periods (2, 5, and 10 min). Treated sprouts were preserved at 5°C and 85-95% relative humidity for 6 days. Irradiation for 10 min effectively reduced fresh weight loss, electrolyte leakage, and microbial count and maintained the firmness of sprouts. It also positively influenced the bioactive components, including antioxidants, total phenols, and protein, potentially providing health benefits to consumers. In addition, prolonged UV-C exposure for 10 min leads to oxidative stress, marked by a rise in malondialdehyde, proline, and hydrogen peroxide content. These compounds assist in stress reduction and preserve secondary metabolites. This research implies that postharvest 10 min UV-C irradiation offers a potential approach to uphold quality while maximizing the nutritional value of mung bean sprouts.